2014
DOI: 10.1044/2014_lshss-13-0035
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Language and Speech in Children Who Were Internationally Adopted at Different Ages

Abstract: Three years after adoption, age of adoption did not influence language or speech outcomes, and most children reached age-expected language levels. Expressive syntax as measured by MLU was an area of relative weakness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…It is possible that benefits of the program on receptive language might be seen in younger children, as receptive language typically develops prior to expressive language. At 4 years of age, the children's receptive language may have a slower rate of increase, because the initial dramatic increases in receptive language in English have already been experienced as seen in other studies investigating acquisition of language (e.g., Glennen et al 2014). Thus, the time frame of the study may not have been long enough to document this growth over time.…”
Section: Receptive Languagementioning
confidence: 58%
“…It is possible that benefits of the program on receptive language might be seen in younger children, as receptive language typically develops prior to expressive language. At 4 years of age, the children's receptive language may have a slower rate of increase, because the initial dramatic increases in receptive language in English have already been experienced as seen in other studies investigating acquisition of language (e.g., Glennen et al 2014). Thus, the time frame of the study may not have been long enough to document this growth over time.…”
Section: Receptive Languagementioning
confidence: 58%
“…Children who change languages during critical periods in learning may have difficulty learning to notice phonemic or grammatical patterns in the new language. Similarly, Glennen (2014) found that children adopted from Eastern Europe had low average mean length of utterance (MLU) scores when assessed 3 years after adoption. Bilingual adults who learned a second language (L2) at young ages and were perceived by monolingual speakers of L2 as having "native-like" conversational language consistently scored below monolingual adults when given extensive tests of language perception, comprehension, and production (Abrahamson & Hyltenstam, 2009;Hyltenstam et al, 2009).…”
Section: Relative Differences In Grammar and Syntaxmentioning
confidence: 95%
“…Glennen (2014) previously determined that 3 years after adoption, age of adoption did not correlate with language outcomes. The reassessment was timed to take place 12-18 months after the age 5 assessment.…”
Section: Assessment Procedures and Data Analysismentioning
confidence: 95%
See 2 more Smart Citations